Penerapan Model Cooperative Learning Tipe Jigsaw Untuk Meningkatkan Keterampilan Problem Solving Siswa Tentang Konsep Masalah Sosial dalam Pembelajaran IPS - Qory Nur Khofifah; Encep Supriatna (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2022)
Social studies learning can develop students in understanding the conditions that occur in society, especially on social problems and knowing past lives in accordance with people's lives. However, expectations in reality show that schools have not been able to understand the demands of community development. Researchers found problems at the time of the study, researchers found problems, namely the lack of social studies learning outcomes for students in class V which showed that many students did not reach the KKM. Which is due to the limited knowledge of teachers about the social studies problem-solving approach, because basically it only uses the lecture method, so that students are less active in the learning process, are less able to realize knowledge in concrete life, are less able to develop their interests, students' critical thinking skills cannot be developed so also the reasoning power of students which ultimately results in low student learning. The study was conducted on 41 students of the fifth grade of the Mangunreja State Elementary School. Two cycles have been carried out with the method used in this research, namely the Class Action Research (CAR) method. The instruments used in the researcher are guide sheets for student tests, sheets for student observations, sheets for teacher observations. The results showed that there was an increase in student learning outcomes. This increase is shown in the results of observations of student activities in the first cycle of activities, the average score of the percentage value is 38.4%, while the average score of the presentation value in the second cycle is 67.6%. This can be seen by the acquisition of scores indicating that there is an increase in student learning activities in social studies lessons using the jigsaw type of cooperative learning model.